Entrepreneurial Clusters and the Co-agglomeration of Related Industries: Spinouts in Portuguese Plastics and Molds - Rui Baptista; Carla Costa (European Regional Science Association (ERSA), 2014)
The success of ?entrepreneurial clusters' has led policymakers towards extensive efforts to seed local entrepreneurship. A particularly important determinant of the ?supply of entrepreneurs' are industry linkages within cities or regions. Indeed, studies consistently find that the most powerful predictor of future entrepreneurship for a city or region is the presence and strength of incumbent firms in the same or in related industries. This study examines how co-agglomeration (or collocation) of entrepreneurial firms in related industries influences cluster growth. Two types of effects are considered that may drive collocation: the inheritance of capabilities from local incumbents by spinout founders; and agglomeration benefits stemming from local access to supply-side spillovers. These effects are examined for the Portuguese molds and plastics industries. If agglomeration economies explain industry collocation, one would expect firms from related industries to collocate in the agglomerated region. Firms locating in the agglomerated region should perform better than firms located elsewhere, independently of their background. If heritage is the main force behind collocation, then spinouts will locate close to parent firms regardless of their region of origin. Spinouts from parent firms in the same or a related industry perform better than other startups. Our methodology is twofold. We first present a historical account of the evolution of the Portuguese molds and plastics industries, focusing on the location and genealogy of firms. Second, we conduct an econometric analysis of detailed data on firms, founders, and workers in the Portuguese molds and plastics industries covering the period 1986-2009. In order to test the predictions derived from agglomeration and organizational heritage theories, two main types of models are estimated, regarding: I. the probability of firms in molds and plastics industries cross-spawning entrants in those industries; II. the determinants of the performance of entrants, according to their geographical origin and founder background (i.e. spinouts vs. independent startups), using survival and sales growth models. Results suggest that the transmission of capabilities from parent firms to spinouts locating in the same region is the foremost driver of collocation and performance for the molds and plastic injection industries. The presence of the plastics industry has a positive impact on the molds industry but not the inverse, implying that while collocation with molds is not a requirement for the plastics industry to flourish, collocation with plastics is important for the molds industry.
Keywords: L26; M13; R30; 330; Clusters; Spinouts; Regional development; Agglomeration Economies; Organizational Heritage